The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1364/oe.23.011657
|View full text |Cite
|
Sign up to set email alerts
|

Ultrabroad terahertz bandpass filter by hyperbolic metamaterial waveguide

Abstract: We propose and demonstrate an ultrabroad terahertz (THz) bandpass filter (BPF) by integrating two different-sized tapered hyperbolic metamaterial (HMM) waveguides, each of which has wide but different absorption and transmission bands, into a unit cell. With proper structural design of each HMM waveguide to control the absorption and transmission bands, we numerically demonstrate the designed BPF is capable of operating with a broad passband in the THz domain. A typical TM-polarized HMM BPF has a peak transmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…As an important part of terahertz functional devices, terahertz broadband filters have important research significance in terahertz technology applications such as medical imaging, security inspection, and product inspection. At present, the main categories of terahertz broadband filters are mainly focused on photonic crystal filters [1], plasma filters [2], and meta-material filters [3][4][5][6][7][8][9]. Photonic crystal filters mainly have terahertz broadband filters with low center-bands and narrow bands with multiple peaks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an important part of terahertz functional devices, terahertz broadband filters have important research significance in terahertz technology applications such as medical imaging, security inspection, and product inspection. At present, the main categories of terahertz broadband filters are mainly focused on photonic crystal filters [1], plasma filters [2], and meta-material filters [3][4][5][6][7][8][9]. Photonic crystal filters mainly have terahertz broadband filters with low center-bands and narrow bands with multiple peaks.…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, Singapore National University et al [4] used a flexible substrate to achieve a broadband filtering effect using polyethylene naphthalate (PEN) as a substrate, overlapping the multi-layer loop structure and fabricating a broadband filter. Among the abovementioned filters, Xuetong Zhou et al [6] designed an ultra-wideband terahertz band-pass filter with a double-cone filter (DCF) with a 3-dB bandwidth of 2.2 THz and a center frequency of about 4.07 THz. The filter's highest transmittance was nearly 37%.…”
Section: Introductionmentioning
confidence: 99%
“…spectral bands [13][14][15][16][17][18][19][21][22][23][24][25][26][27], and there are only a few studies on selective absorption enhancement of HMMs.…”
Section: Design Principlesmentioning
confidence: 99%
“…It has been shown that HMMs can be used to enhance light absorption due to their high-k modes and divergent photonic density of states [4,12]. To date, many efforts have been made to improve light absorption of HMMs with the absorption wavelengths covering the microwave [13], terahertz [14][15][16], infrared [17][18][19][20][21][22] and visible wavelength regions [23][24][25][26][27]. In real applications, selective absorption enhancement is highly desired in fields such as thermal radiation tailoring [28], sensitive detection [29] and sensing [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation